One-pot synthesis of highly active Ni/Fe nano-bimetal by simultaneous ball milling and in situ chemical deposition. Issue 47 (25th July 2018) - Zhang, Shuo-Shuo; Yang, Ning; Ni, Shou-Qing; Natarajan, Vinothkumar; Ahmad, Hafiz Adeel; Xu, Shiping; Fang, Xu; Zhan, Jinhua
Abstract : In this study, nanoscale bimetallic particles (Ni/Fe) were prepared by a simultaneous ball milling and in situ chemical deposition process (B&C) with high dechlorination activity for 4-chlorophenol (4-CP). Abstract : In this study, nanoscale bimetallic particles (Ni/Fe) were prepared by a simultaneous ball milling and in situ chemical deposition process (B&C) with high dechlorination activity for 4-chlorophenol (4-CP). The results suggest that the introduction of Ni significantly improved the dechlorination of 4-CP. The dechlorination activity of Ni/Fe-B&C ( k obs = 0.168 min −1 ) was increased significantly with a lengthening of the milling time and showed maximum activity at the milling time of 4 h. Bimetals prepared with the incorporation of Ni into Fe can quickly and completely dechlorinate 4-CP within 90 min reaction time. The dechlorination activity was mainly attributed to the synergistic effects of Ni and Fe. The dechlorination rate was increased with increasing Ni–Fe dosage but decreased with increasing solution pH and 4-CP concentration. Ni/Fe-B&C catalyst could be reused 10 times at pH below 5.0. This approach could offer great opportunities for both research and industrial applications to eliminate chlorinated organic pollutants.